Assessing Forest Cover Loss Using Landsat Images and GIS: A Case Study in Colombian Protected Area (2022)
The Corchal “El Mono Hernández” Fauna and Flora Sanctuary is a protected area located in northern Colombia and is home to the Pterocarpus officinalis forest. In this area, however, this forest cover is declining due to natural causes associated with a change in the hydrosedimentological dynamics. Multitemporal assessment was performed to quantify the forest loss. Landsat images from the years 1986, 1998, 2003, 2013, and 2018 were downloaded and a supervised classification was performed using four cover classes: “Pterocarpus officinalis,” “other vegetation,” “waterbody,” and “bare land.” The results showed that the vegetation cover of Pterocarpus officinalis forest had an initial extent of 865.26 ha in 1986; for the 1986–1998 period, the reduction was 60.30 ha; for the 1998–2003 period, it was 399.15 ha; and for the 2003–2013 period, it was 78.30 ha. Contrary to previous periods, in the 2013–2018 period, 79.65 ha of forest was recovered. In conclusion, Pterocarpus officinalis forest lost approximately 50% of its cover during the 1986–2018 period. This information is of great importance for government and management entities for decision-making in the conservation and restoration of this forest. © 2022 Taylor & Francis.